Caffeine Affects Time to Exhaustion and Substrate Oxidation during Cycling at Maximal Lactate Steady State - de Oliveira Cruz, Rogério Santos (Nutrients, 2015)
This study analyzed the effects of caffeine intake on whole-body substrate metabolism and exercise tolerance during cycling by using a more individualized intensity for merging the subjects into homogeneous metabolic responses (the workload associated with the maximal lactate steady state—MLSS). MLSS was firstly determined in eight active males (25 ± 4 years, 176 ± 7 cm, 77 ± 11 kg) using from two to four constant-load tests of 30 min. On two following occasions, participants performed a test until exhaustion at the MLSS workload 1 h after taking either 6 mg/kg of body mass of caffeine or placebo (dextrose), in a randomized, double-blinded manner. Respiratory exchange ratio was calculated from gas exchange measurements. There was an improvement of 22.7% in time to exhaustion at MLSS workload following caffeine ingestion (95% confidence limits of ±10.3%, p = 0.002), which was accompanied by decrease in respiratory exchange ratio (p = 0.001). These results reinforce findings indicating that sparing of the endogenous carbohydrate stores could be one of the several physiological effects of caffeine during submaximal performance around 1 h.